Emergency Foot Fillet Free Flap Based on Posterior Tibial Vessels for Reconstruction of Contralateral Heel and Sole: A Unique Spare Part Surgery - Venkatramani, Hari; Patel, Smitkumar K.; Mohan, Monusha; Muthukumar, Vamseedharan; Sabapathy, S Raja (Journal of Hand and Microsurgery, 2022)
Introduction Reconstruction of the sole is an extremely challenging problem for a reconstructive microsurgeon. The specialized nature of its skin and subcutaneous tissue makes reconstruction arduous. When posed with complex bilateral lower extremity trauma where one limb was nonsalvageable, we harvested the uninjured foot fillet flap for free flap cover to reconstruct the contralateral sole. We report two such cases with follow-up assessment.Patients and Methods Two cases of sole reconstruction with emergency foot fillet free flap scavenged from the amputated contralateral limb were retrospectively analyzed. In both the patients, foot fillet free flap based on the posterior tibial neurovascular bundle was used. The follow-up assessment data collected included flap status, presence of any complications and prosthesis use, and functional status of the limbs at final follow-up.Results Both the free flaps survived. Postoperative period was uneventful. No complications such as wound infection, delayed healing, flap necrosis, or scar breakdown were noted. The plantar flaps had recovery of protective sensation. Both the patients are ambulant; the first man with a fitted prosthesis and the second woman with the aid of a walker.Conclusion The opportunity to utilize spare tissue from the amputated limb should be seized. Loss of the plantar aspect of foot poses a real challenge. The plantar foot fillet free flap is a durable flap with preservation of plantar sensations. It is probably the best choice as it replaces “like with like.” Prerequisites for utilizing the “spare part surgery” concept are meticulous initial debridement as well as emergency free tissue transfer, which require senior input and excellent infrastructure.
Keywords: reconstructive; surgical; amputation; foot fillet flap; free flaps; leg injuries; microsurgery